First 72 Hours of Humanitarian Assistance for Flash Flood Victims in Central Sulawesi - Hafid, Fahmi; Nasrul, Nasrul; Faisal, T. Iskandar; Nurmiaty, Nurmiaty; Nurjaya, Nurjaya; Sumiaty, Sumiaty; Aminuddin, Aminuddin; Sudarman H Melangka, Yulianus; Taqwin, Taqwin; Sariman, Sarina; Hamsiah, Hamsiah; Ramadhan, Kadar (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
The first 72 hours is a very important golden period in emergency response. Effectiveness of saving victims of flash floods and individual ability to survive, as well as body energy reserves. Assistance to victims of flash floods in Balinggi District, Parigi Moutong Regency, Central Sulawesi Province was provided because the number of victims was quite large and there was an urgent need. Provision of humanitarian assistance directly to victims of flash floods and also through the BPBD Command post in Parigi Mautong district. Assistance in the form of mineral water, rice, chicken eggs, cooking oil, granulated sugar, pop noodles, soy sauce, tomato sauce, wafers, honey, eucalyptus oil, and pampers, the number of beneficiaries is around 30 people consisting of toddlers, pregnant women, nursing mothers, elderly. Implementation of activities on June 2 until 3, 2023 three days after the flash floods hit. The volunteer team consisted of 7 lecturers, staff, and students from the Poltekkes Kemenkes Palu. The assistance was received at the BPBD Command Post in Parigi Moutong Regency properly and on time.